The Malayan Indian Congress and Early Political Rivalry Among Indian Organisations in Malaya, 1946-1950 - Shanthiah Rajagopal; Joseph Milton Fernando (Kajian Malaysia, 2018)
The Malayan Indian Congress (MIC) emerged amid the chaos of the immediate postwar period in Malaya to represent the interests of the minority Indian community. Several Indian leaders who had been involved in the Indian Independence League during the war decided that a national organisation was needed to serve as the voice of the Indian community. Within a few years, the party became the leading representative of the Indian community. But the MIC's transformation was not without serious challenges from within and from other Indian political movements. This article examines the early period of the party's history to trace the growth of the MIC into the leading political movement of the Indians in Malaya, its internal problems and significant rivalry with other Indian-based organisations during this period and the issues that arose. The article shows that a pragmatic approach by the party leadership, in particular its discontinuance of the boycott of the 1948 Federation Constitution and its principled position on citizenship, enabled the party to overcome the challenge posed by rival Indian organisations to become the leading voice of the Indians by 1950.